PENGARUH PROFITABILITY, LIQUIDITY, UKURAN PERUSAHAAN DAN LEVERAGE TERHADAP NILAI PERUSAHAAN BIDANG INDUSTRI DALAM SEKTOR KONSUMSI YANG TERDAFTAR DI BEI PERIODE 2018-2021 - Barita, Gilbert Austin; Ekadjaja, Agustin (Fakultas Ekonomi, Universitas Tarumanagara, 2025)
This study aims to observe and assess the effect of profitability, liquidity, leverage and firm size on firm value in manufacturing companies in the consumption sector listed on the Indonesia Stock Exchange (IDX) (in an empirical study in the 2018-2021 period. This study uses 16 manufacturing companies from the consumption sector have been selected by purposive sampling method with a total of 64 data for the last four years. The data used is secondary data in the form of financial statements ending on January 1 in a certain period. The data in this study uses the IBM SPSS statistical software 22. The results of the study state that profitability has a significant positive effect on firm value, liquidity has an insignificant positive effect on firm value, while firm size and leverage have a significant negative effect on firm value. to the value of the company.